EFEKTIVITAS MANAJEMEN SISTEM PENDIDIKAN DAN PELATIHAN PRAJABATAN APARATUR PEMERINTAH GOLONGAN III (Studi Kontribusi Komponen-Komponen Proses Belajar Mengajar Terhadap Efektivitas Sistem Pembelajaran dan Dampaknya Terhadap Kinerja Lulusan di Propinsi Jawa Barat) - Adang Kurniadi (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2010)
This research focuses on the teaching learning process of Level III Pre-service Training among West Java Provincial, Municipal and Regency Boards, Offices and Organization Units of Local Personnel Board. The research identifies the effectiveness of the Level III Pre-service Training Management, both from the input and its impact. The input comprises the components of teaching learning process consisting of raw input (participant characteristics), instrumental and environmental inputs, their influence to the learning effectiveness, and impacts to the alumni performance. This research employs a quantitative method. Thedata are collected through observation, interview, questionnaires and library research. The data are then analyzed and described by using scoring analysis (weight mean score model) and path analysis model. The result shows that the whole components of teaching learning process, the learning effectiveness, and the alumni performance do not reach the ideal condition as expected. Meanwhile, the inductive analysis reveals that partially as well as holistically the participant characteristics and instrumental and environmental inputs have a positive and significant effect to the effectiveness of learning system. In general, the Level III Pre-service Training system does not run effectively so that it does not gives optimal contribution to alumni performance. Thus, measures need to be taken to improve the input, process, output, and outcome of Level III Pre-service Training system conducted by West Java Regional Training Office and other related training institutions.